The effectiveness of internal and external auditing in support Corporate governance - الدوغجي علي حسين (Journal of Economics and Administrative Sciences, 2009)
The study aims at showing the active role of the internal auditors through explaining what they should be obliged to in writing the reports and financial and non financial statements according to the international standards of accounting to be transparent and integral. It also aims at giving the independence that the auditors should enjoy through connecting them to an Auditing Commissions to submit additional services in addition to assessing the instrument of control to evaluate risks, give consultations and the services related to the governance and independence of Supervising Council. The process of external auditing should render the auditors the sufficient vocational care with obligation to the rotation each (3-5) year and activate the preview who acts as an auditor. That would enable and improve the total quality of the process for external. Also, the study aimed at showing the concept of governance which is based on the base of organizing the relationship between the Board of the companies and Executive Managers and between the commission of auditing in the board and the shareholders of interest holders with the company and the auditors in the second place. Thus, the interaction between the internal and external auditors will be reflected on the board through the preparation of financial and non-official reports in integrity. Consequently, this will stop the fraud of the management on the accounting regulations and rules. Then, it will contribute to the raise of the efficiency of risk assessment and the generation of real value of the company through reaching into wise governance. The research comes up to the following findings: • The activity of internal auditing is regarded as one of the activities that support governance. The demand has been on the services of qualified internal auditors. • The bureaus of auditing have in affirming the validity of the financial bills and reports published to serve the society through the quality of the service offered and activate the process of rotation and the testing of the counter part. The difficulty of applying governance is not the reason of law, but in how applies this law. The morals are matters cannot oblige the others to. They are personal gains flowing from many social factors governed by religion, education and the environment.